Agent based model for measuring the implication of technological change on telecentre's operation - Ab. Aziz, Azizi; Ahmad, Faudziah; Yusop, Nor Iadah; Mat Aji, Zahurin (2016)
Technological change (TC) can be seen as the driving force of the telecentres’ operation. However, telecentres’ poor usage and operation arises concerns on the continued relevance of these centres. Evidence on its impacts are needed so that budget allocation for resources and program improvements can be justified.The paper aims to present an agent-based model that was developed to show the impact of TC on telecentre's usage.Results on the effective usage of telecentre in different types of scenarios were shown. Mathematical verification technique was used to evaluate the simulation model.The corresponding relations established showed that long term effectiveness can be realized through the impact of either Long term utilization or Long term satisfaction which when accumulated over time yield Long term effectiveness